Cryptotanshinone attenuates LPS-induced acute lung injury by regulating metabolic reprogramming of macrophage - Ye, Zesen; Wang, Panxia; Feng, Guodong; Wang, Quan; Liu, Cui; Lu, Jing; Chen, Jianwen; Liu, Peiqing (Frontiers in Medicine, 2023)
Acute lung injury (ALI) is a life-threatening inflammatory disease without effective therapeutic regimen. Macrophage polarization plays a key role in the initiation and resolution of pulmonary inflammation. Therefore, modulating macrophage phenotype is a potentially effective way for acute lung injury. Cryptotanshinone (CTS) is a lipophilic bioactive compound extracted from the root of Salvia miltiorrhiza with a variety of pharmacological effects especially the anti-inflammatory role. In this study, we investigated the therapeutic and immunomodulatory effects of CTS on ALI. One dose intratracheal instillation of LPS (5 mg/kg) successfully induced in vivo ALI model and LPS (1 μg/mL) was used to induce inflammatory responses in RAW264.7. Our results showed that CTS effectively alleviated pulmonary inflammation and improved ALI. Both in vivo and in vitro results revealed that CTS inhibited the differentiation of macrophage into M1 phenotype and promoted polarization into M2 phenotype during ALI. Mechanically, CTS blocked LPS-induced metabolic transformation of macrophages by activating AMPK. In conclusion, our results indicated that CTS effectively played an anti-inflammation role during ALI and might be a novel strategy for the treatment of ALI.